Musculoskeletal work in high bar progressions - Irwin, G.; Kerwin, D. G. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This study explained and assessed the similarity in joint kinetic profiles between the longswing (LS) and four progressions. Video recordings of four male gymnasts performing the LS and four progressions were quantified using 2D DLT techniques on an instrumented high bar. Inverse dynamic analyses quantified the muscle moments and work done at hips and shoulders. RMSD analysis between the work during the LS and progressions was used to group the progressions based on overall level of similarity to the LS. The least similar progression was the looped bar pendulum swing, whilst the most similar was the bent knee LS. This study has identified that progressions can be classified into those that are similar in terms of physical demand or movement pattern. This study raises the question should progressions be selected based on its kinetic or kinematic similarity to the target skill.